2011
DOI: 10.1111/j.1532-950x.2011.00856.x
|View full text |Cite
|
Sign up to set email alerts
|

An Ex Vivo Biomechanical Study Comparing Strength Characteristics of a New Technique with the Three‐Loop Pulley for Equine Tenorrhaphy

Abstract: The 10-strand Savage technique for repair of transected cadaver SDF tendons has superior strength characteristics with or without the epitenon suture when compared to the 3-loop pulley. Suture material and pattern interactions were observed with PG 910 conferring higher strength for the 10-strand Savage whereas PDS did so for the 3-loop pulley.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
41
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(47 citation statements)
references
References 20 publications
5
41
0
1
Order By: Relevance
“…Mean peak strength values documented in this study (287.7 N for the double locking loop suture with polypropylene and 237 N for the single locking loop pattern with epitendon suture using polyglactin, respectively) are in agreement with reported maximum values (Smith et al, 2011).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Mean peak strength values documented in this study (287.7 N for the double locking loop suture with polypropylene and 237 N for the single locking loop pattern with epitendon suture using polyglactin, respectively) are in agreement with reported maximum values (Smith et al, 2011).…”
Section: Discussionsupporting
confidence: 89%
“…Based on suture peak strength, tendon plates (1500 N) provide the most robust experimental method for tendon repair, followed by the triple loop (313 N) and double loop (155 N) suture patterns (Smith et al, 2011). Mean peak strength values documented in this study (287.7 N for the double locking loop suture with polypropylene and 237 N for the single locking loop pattern with epitendon suture using polyglactin, respectively) are in agreement with reported maximum values (Smith et al, 2011).…”
Section: Discussionsupporting
confidence: 86%
“…A recent study investigating the overall outcome after lacerations of the flexor tendons, suspensory ligament, or distal sesamoidean ligaments in horses found that 54–55% of horses returned to an equal level of performance and 24–27% returned to a lower level of performance . Primary repair of tendon lacerations is recommended to facilitate healing by maintaining apposition of viable tendon ends until the repair can withstand physiologic tensile loading . Although several tendon repair methods have been proposed, an ideal repair technique has not been identified and successful repair is often not achieved.…”
mentioning
confidence: 99%
“…Goals of a successful tenorrhaphy include creating a strong repair, with minimal gap formation, reduced bulk at the repair site, minimal adhesion formation, and little disruption of blood supply. To date, there is no repair technique described in vivo that prevents gap formation . Normal equine superficial digital flexor tendons (SDFT) have been reported to support a tensile load of 1845‐3559 N at a walk .…”
mentioning
confidence: 99%
“…The failure stress is fundamentally simple to measure, where a constant load is applied to a tissue and the progressive time dependant elongation is measured (Smith & Webbon 1996). However, the load to failure represents the continuous loading of a tendon sample till complete rupture (Woo et al 1997;Smith et al 2011).…”
Section: Biomechanical Properties Of the Digital Flexor Tendonsmentioning
confidence: 99%